1979
DOI: 10.1007/bf00414614
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the arginine and arginase of tears in experimentally-induced herpes simplex corneae

Abstract: Experimental corneal herpes is always accompanied by the accumulation of arginine, the substrate of arginase, in tears, ensuring the multiplication of the herpes hominis virus. The main source of the large amount of arginine is the desquamating corneal epithelium, since after the epithelium of the cornea is abraded the arginine content of the tears again equals that of healthy tears. The low arginase content of rabbit tears can be supplemented by arginase applied as eyedrops, and this results in the cure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In addition, arginase 1 metabolism appeared to increase 10 fold in a murine model of HSV-1 induced stromal keratitis infection, 12 suggesting a correlation with symptom resolution and arginine levels. Kahan et al also found that corneal herpes was accompanied by the accumulation of arginine in the corneal epithelium, a potential finding which they attributed to increased viral replication and virulence 13 . Furthermore, the addition of topical ocular arginase led to a resolution of the herpetic episode, further substantiating arginine's role in infection and disease progression 13 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, arginase 1 metabolism appeared to increase 10 fold in a murine model of HSV-1 induced stromal keratitis infection, 12 suggesting a correlation with symptom resolution and arginine levels. Kahan et al also found that corneal herpes was accompanied by the accumulation of arginine in the corneal epithelium, a potential finding which they attributed to increased viral replication and virulence 13 . Furthermore, the addition of topical ocular arginase led to a resolution of the herpetic episode, further substantiating arginine's role in infection and disease progression 13 …”
Section: Discussionmentioning
confidence: 97%
“…Kahan et al also found that corneal herpes was accompanied by the accumulation of arginine in the corneal epithelium, a potential finding which they attributed to increased viral replication and virulence 13 . Furthermore, the addition of topical ocular arginase led to a resolution of the herpetic episode, further substantiating arginine's role in infection and disease progression 13 …”
Section: Discussionmentioning
confidence: 97%
“…It has been hypothesized that the eye maintains its immunoprivilege and avascularity by keeping arginine at low levels (Fu et al, 2011). During HSV infection of the eye, disease progression correlates with increased arginine levels (Kahan et al, 1979). In this regard, peg-ArgI has potential to modulate these deleterious disease-associated sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments show that herpes does not grow without Arg [53] , [54] , [55] , as Arg is a key building block of the viral envelope that facilitates localization, fusion, and entrance to host cell nuclei [56] , [57] . Arg also seems to promote herpes-associated corneal tumors [58] and was highly concentrated in tears of rabbits with corneal herpes [59] . This is particularly relevant, as 93% of Hawaiian green turtles with FP have ocular tumors [60] ( Fig.…”
Section: Discussionmentioning
confidence: 99%